The Implementation Of Digital Resources As Supporting Learning Media In Teaching Narrative Writing Text - Rani Santika; Dila Charisma; Ikariya Sugesti (Publikasi Indonesia, 2023)
Digital Resources is supporting learning media that utilize technology in delivering material such as video, website, e-book, and slideshows. This research aims to investigates the implementation of digital resources as supporting learning media in teaching narrative writing text. This research used qualitative method by using descriptive qualitative design. The data was obtained through observation and interview. The subject of this research were two English teachers in Vocational High School Ibnu Khaldun at 10th Grade the academic years of 2022/2023 who implemented digital resources in teaching narrative writing text. The research findings of this research show that the English teachers have used digital resources very well, but it still needs to optimize the implementation of digital resources for the further learning